Utopični socialisti - Medved, Primož (Družboslovne razprave, 2018)
Ebenezer Howard, with his book Garden City (1898), is considered to be the initiator of contemporary sustainable urbanism. Few authors recognise utopian socialists, with their socio-spatial visions since the late 18th century, as conceptual pioneers of modern sustainable cities. In the article, specific elements of visions of socialist utopias, which anticipated the basic functionalities of modern sustainable cities, are identified. The study shows how the utopian socialists' plans transmuted into the basic structure of the 21st century sustainable neighbourhood. In addition, the article addresses the debate on whether spatial determinism, as typical of the utopian socialists' visions, is relevant in today's urban sustainable cities. Are communities' long-term relations based on spatial proximity (still/again) an imperative in modern sustainable cities?
Keywords: City planning; Sustainable development; Trajnostni razvoj; trajnostni urbanizem; Urbanizem; Utopian socialism; Utopian socialists; Utopični socialisti; Utopični socializem